THE THE FORMULATION OF KEFIR COW MILK WHIT THE ADDITION OF PAPAYA FRUIT SARI (Carica Papaya. L) AS SUGAR SUBSTITUTE INGREDIENTS - Yulianti .; Retno Budi Lestari; Marjoko Purnomosidi (Jurnal Sains Pertanian Equator, 2020)
The purpose of this study was to determine the addition of papaya juice as a sugar substitute for the physicochemical chemistry of cow's milk kefir. The study was conducted at the Laboratory of Animal Husbandry at the Faculty of Agriculture, Tanjungpura University in Pontianak, the Laboratory of Agricultural Product Technology at the Faculty of Agriculture at Tanjungpura University, Pontianak and the Pontianak State Polytechnic Fisheries Laboratory. The research design used was a Completely Randomized Design (CRD) with 5 treatments and 5 replications each treatment was P0 = Control (without adding papaya juice), P1 = Adding papaya juice 2% of cow's milk kefir, P2 = Adding juice papaya fruit 4% from cow milk kefir, P3 = addition of papaya fruit juice 6% from cow milk kefir and P4 = addition of papaya fruit juice 8%. The parameters observed were pH, total acid, ethanol content and viscosity. The average pH, total acid, ethanol content and the highest viscosity are: 3.99, 4.79, 2.04 and 2963.36, which are found in different treatments. The conclusion of this study is that the addition of papaya juice can improve the quality of cow's milk kefir. Keywords: Cow's milk, Kefir and Papaya seeds.